2013
DOI: 10.1155/2013/254239
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity Assessment of Multispecies Probiotics Using Reverse Mutation, Mammalian Chromosomal Aberration, and Rodent Micronucleus Tests

Abstract: Genotoxicity assessment is carried out on freeze dried powder of cultured probiotics containing Lactobacillus rhamnosus LCR177, Bifidobacterium adolescentis BA286, and Pediococcus acidilactici PA318. Ames tests, in vitro mammalian chromosome aberration assay, and micronucleus tests in mouse peripheral blood are performed. For 5 strains of Salmonella Typhimurium, the Ames tests show no increased reverse mutation upon exposure to the test substance. In CHO cells, the frequency of chromosome aberration does not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…TA98 and TA100 possessed all endogenous characteristics, whereas TA102 had no mutation on uvrB (οuvrB). TA1535 and TA1537 contained no plasmid that rendered ampicillin and tetracycline resistance, which were all consistent with previous reports [5] , [15] .…”
Section: Resultssupporting
confidence: 90%
“…TA98 and TA100 possessed all endogenous characteristics, whereas TA102 had no mutation on uvrB (οuvrB). TA1535 and TA1537 contained no plasmid that rendered ampicillin and tetracycline resistance, which were all consistent with previous reports [5] , [15] .…”
Section: Resultssupporting
confidence: 90%
“…paracasei , and L . rhamnosus , have been reported not to induce a significant increase in the frequency of mammalian cells with CAs when compared with the positive control [27, 30, 31]. However, L .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to demonstrating the efficacy of probiotics in improving human health, safety characteristics must be taken into consideration. It has been reported that lactic acid bacteriacultured skim milk has antimutagenic activity (Hosono et al, 1986), that a multispecies probiotic mixture does not have mutagenic effects on various organisms (Chiu et al, 2013), and that LP20 powder made from heat-killed Lactobacillus plantarum L-137 has no genotoxic properties both in vitro and in vivo (Hirose et al, 2009). Nonetheless, new isolate-specific species or strains of probiotics (novel probiotics) cannot be assumed to share the historical safety of traditional strains (Salminen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%